2019
DOI: 10.15330/pcss.20.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of Co3C carbide with carbon nanotubes

Abstract: Nanoscaled (about 15 nm of size) metastable carbide Co3C was synthesized in a high-energy planetary ball mill by mechanical alloying of a mixture of powder cobalt (75 at. %) and multiwalled carbon nanotubes (CNT, 25 at. %). Phase transformation takes place at reaction milling according to the reaction hcp-Co + CNT ® Co3C (reaction time is 120 - 220 min). The crystal structure of the Co3C carbide formed in the milling products was studied by X-ray diffraction method. It has revealed that the Co3C phase crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…5,[14][15][16][17][18][19][20][21][22] Experimental and theoretical studies have conrmed its notable magnetization strength and coercivity, suggesting that it could serve as an ideal rare-earth-free permanent magnet material with promising developmental prospects. 5,14 Co 3 C nanoparticles have been synthesized using methods like wet chemical synthesis, 5,23,24 mechanical alloying, 3,6,25 ion irradiation, 26 and the one-pot template-free solvothermal approach. 27 P. V. Marshall et al utilized a DAC (diamond anvil cell) device with a size of 300 mm to synthesize microscale Co 3 C under conditions of 5-15 GPa and 1200 K. 28 However, stable carbides are not present in the Co-C system.…”
Section: Introductionmentioning
confidence: 99%
“…5,[14][15][16][17][18][19][20][21][22] Experimental and theoretical studies have conrmed its notable magnetization strength and coercivity, suggesting that it could serve as an ideal rare-earth-free permanent magnet material with promising developmental prospects. 5,14 Co 3 C nanoparticles have been synthesized using methods like wet chemical synthesis, 5,23,24 mechanical alloying, 3,6,25 ion irradiation, 26 and the one-pot template-free solvothermal approach. 27 P. V. Marshall et al utilized a DAC (diamond anvil cell) device with a size of 300 mm to synthesize microscale Co 3 C under conditions of 5-15 GPa and 1200 K. 28 However, stable carbides are not present in the Co-C system.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical alloying has recently been gaining increasing application due to the possibility of obtaining novel nanoscale materials with an interesting set of functional properties. Previously we have successfully synthesized such well-known d-metal carbides as TiC, ZrC, HfC, VC, NbC, TaC, Mo2C, W2C, WC, Fe3C and Co3C using multi-walled carbon nanotubes (CNTs) as a carbon component of the charge [1][2][3][4][5]. It was also shown that the crystal structures of the carbides obtained have certain features in the atoms arrangement [5].…”
Section: Introductionmentioning
confidence: 99%